2016
DOI: 10.1159/000446173
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Insulin-Like Growth Factor-1 via Nitric Oxide Production in a Hypergalactosemic Model of Neonate Skin Fibroblast Cultures

Abstract: Background: Galactosemia is a severe metabolic disorder known to cause hepatosplenomegaly, jaundice and cataracts in neonates, and many patients develop later complications such as mental retardation, disorders of motor function or speech, and hypergonadotrophic hypogonadism. The pathogenetic mechanisms of classical galactosemia are unclear; however, nitric oxide (NO) has been suggested to play a role. Objectives: Insulin-like growth factor-1 (IGF-1) is important for the growth and development of children, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It can be assumed that D-gal induces skin aging in two ways: the direct impact of D-gal on skin cells and/or the indirect effect associated with the accumulation of toxic metabolites in the skin. Our understanding at this age leads us to suggest that cytotoxicity of D-gal is based on activated oxidative stress, as confirmed by the in vitro [65,[111][112][113][114][115][116][117][118]144] and in vivo experiments [70, 72-74, 76, 78, 82-85].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It can be assumed that D-gal induces skin aging in two ways: the direct impact of D-gal on skin cells and/or the indirect effect associated with the accumulation of toxic metabolites in the skin. Our understanding at this age leads us to suggest that cytotoxicity of D-gal is based on activated oxidative stress, as confirmed by the in vitro [65,[111][112][113][114][115][116][117][118]144] and in vivo experiments [70, 72-74, 76, 78, 82-85].…”
Section: Discussionmentioning
confidence: 81%
“…In case of metabolic dysfunction or a very high level of galactose, it was established that Gal-1-P accumulates in different tissues [142], including skin fibroblasts [143] of galactosemic patients exposed to galactose. Recent studies have shown that the treatment of neonate skin fibroblast cultures with Gal-1-P significantly enhanced cellular levels of NO and inducible nitric oxide (iNOS) more than galactose treatment [144]. In addition, Gal-1-P downregulates expression of insulin-like growth factor 1 (IGF-1) [144].…”
Section: Molecular Mechanisms Of D-gal-inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This imbalance of metabolite levels may lead to glycosylation defects, endoplasmic reticulum (ER) stress, and oxidative stress. [3][4][5] Ultimately, this disease results in inflammation, tissue damage, and other phenotypes as seen in untreated infants including liver and kidney failure, cataracts, and death. 1,2 Standard newborn screening and a diet low in galactose content has largely eliminated such dire Click here to access the podcast for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in GALT activity results in the buildup of galactose, galactose‐1‐phosphate, and galactitol as well as an imbalance in UDP‐glucose and UDP‐galactose 1,2 . This imbalance of metabolite levels may lead to glycosylation defects, endoplasmic reticulum (ER) stress, and oxidative stress 3‐5 . Ultimately, this disease results in inflammation, tissue damage, and other phenotypes as seen in untreated infants including liver and kidney failure, cataracts, and death 1,2 .…”
Section: Introductionmentioning
confidence: 99%